Effects of leadership styles and motivational factors on worker engagement: an empirical study on the ready-made garments industry in Bangladesh - Hossan, Dalowar; Mansor, Zuraina; Al Mamun, Mohammad Abdullah; Mohammad Saif, Abu Naser; Jantan, Amer Hamzah (Inderscience Publishers, 2022)
This study inspects the effects of motivational factors (intrinsic and extrinsic) and leadership styles (transformational and transactional) on worker engagement in the ready-made garments industry of Bangladesh. The paper is based on Herzberg's motivation-hygiene theory. The study adopted a quantitative technique and used SPSS to analyse the data assembled from a valid sample of 387 workers in Bangladesh's ready-made garments industry. The findings show that extrinsic motivational factors positively correlate with worker engagement more than intrinsic motivational factors. Consequently, transformational leadership is positively associated with worker engagement more than transactional leadership among the workers in the ready-made garments industry of Bangladesh. In conclusion, it is suggested that the industry should focus more on the transformational leadership style compared to the transactional leadership style and workers have to be motivated to increase productivity in this specific industry.